Neuronal nitric oxide synthase gene transfer decreases [Ca2+]i in cardiac sympathetic neurons. - Wang, L; Henrich, M; Buckler, K; Mcmenamin, M; Mee, C; Sattelle, D; Paterson, D (2007)
Gene transfer of neuronal nitric oxide synthase (nNOS) can decrease cardiac sympathetic outflow and facilitate parasympathetic neurotransmission. The precise pathway responsible for nitric oxide (NO) mediated inhibition of sympathetic neurotransmission is not known, but may be related to NO-cGMP activation of cGMP-stimulated phosphodiesterase (PDE2) that enhances the breakdown of cAMP to deactivate protein kinase A (PKA), resulting in a decrease in Ca(2+) influx mediated exocytosis of the neurotransmitter. We investigated depolarization evoked Ca(2+) influx in nNOS gene transduced sympathetic neurons from stellate ganglia with a noradrenergic cell specific vector (Ad.PRS-nNOS or empty vector), and examined how nNOS gene transfer affected cAMP and cGMP levels in these neurons. We found that targeting nNOS into these sympathetic neurons reduced amplitudes of voltage activated Ca(2+) transients by 44%. nNOS specific inhibition by N-[(4S)-4-Amino-5-[(2-aminoetyl](amino] pentyl]-N'-nitroguanidine (AAAN) reversed this response. nNOS gene transfer also increased intracellular cGMP (47%) and decreased cAMP (29%). A PDE2 specific inhibitor Bay60-7557 reversed the reduction in cAMP caused by Ad.PRS-nNOS. These results suggest that neuronal NO modulates cGMP and PDE2 to regulate voltage gated intracellular Ca(2+) transients in sympathetic neurons. Therefore, we propose this as a possible key step involved in NO decreasing cardiac sympathetic neurotransmission.